PENGARUH TOTAL QUALITY MANAGEMENT, INTERPERSONAL COMMUNICATION DAN SERVICE QUALITY TERHADAP STUDENT SATISFACTION PADA YAYASAN PENDIDIKAN ISLAM MIFTAHUSSALAM MEDAN - HENNY PURNAMA DEWI (JURNAL ILMIAH SIMANTEK, 2020)
Educational institutions are required to improve their quality in fulfilling student satisfaction so that they can create educatedhumans who have high quality life skills. The control system is one of the things that is a weakness in educational institutionsin Indonesia which causes a decrease in student satisfaction with service quality. Therefore, continuous quality improvementmust be emphasized. The purpose of this study is to optimize student satisfaction through a strategy that focuses onimproving quality by implementing Total Quality Management (TQM), supported by good Interpersonal Communication (IC)between teachers and students in achieving maximum service quality. The sample of this research was 100 high schoolstudents / equivalent class XII Islamic Education Foundation Miftahussalam Medan, the sample was taken using nonprobabilitysampling technique with purposive sampling technique. The second order structural equation model is used asthe basis for analysis and method with the SPPS Programs. The results of this study indicate that Total Quality Management,Interpersonal Communication and service quality have a positive and significant effect on student satisfaction.